A medição de desempenho na construção enxuta: estudos de caso - Lorenzon, Itamar Aparecido (2008)
Currently the civil construction sector in under several internal and external pressures, including financing crisis, lack of new public constructions and increasing quality requirements demanded by the client. This environment leaded the companies of this sector to search for new solutions by adopting new organizational and production management practices. Within the alternatives, the Lean Construction, a derivation from the Lean Production, appeared as a way to manage civil construction productivity by reducing the activities that do not add value, by increasing flexibility and by increasing the transparency of the process. This new form of organizing the production brings new concepts that require new forms to measure the performance. In this context, this thesis aims to empirically investigate, applying a qualitative approach and multiple case study, how the companies which implemented the Lean Construction are using the performance measures within this form of production organization and administration. The field research was carried through four civil construction companies which applied Lean Construction principles. The empirical evidences showed that the studied companies had not incorporated all Lean Construction principles, with some of those only starting to be assimilated. Nevertheless, these companies had to modify their performance measures, mainly by creating pointers that evaluated this new form to manage the production. This theses brings a contribution to the civil construction sector by analysing the current use level of Lean Construction principles and by indicating the needed changes on how performance pointers are measured to incorporate this new management way.